2016
DOI: 10.21037/tau.2016.s122
|View full text |Cite
|
Sign up to set email alerts
|

AB122. The structure and function of NKAIN2—a candidate tumor suppressor

Abstract: Objective: To evaluate the clinical efficacy of bladder hydrodistention and intravesical sodium hyaluronate in the treatment of interstitial cystitis (IC). Methods: Twenty-one patients with IC received intravesical sodium hyaluronate therapy under nerve block or intravenous anesthesia. Bladders were perfused with 100 cmH 2 O perfusion pressure and expanded for 10 min and were later injected with 40 mg/50 mL sodium hyaluronate through the catheter. After 1 h, the perfusion fluid was released. Perfusion was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…We speculate that this is likely active but of unclear clinical significance, as ACTN2 has a strong N-terminal homodimerization domain, the prerequisite for ALK activation by fusion (34), and additionally ALK has been reported to be expressed in a high percentage of Ewing Sarcomas (35). Regarding the candidate FOXO1-NKAIN2 fusion, NKAIN2 is a poorly characterized candidate tumor suppressor gene; fusions and translocations that have been previously reported for this protein are typically either inactivating or out-of-frame (36). FOXO1 fusions to PAX3 or PAX7 include the FOXO1 C-terminal transcriptional activation domain (TAD), aberrantly activating PAX3/7 targets (37).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that this is likely active but of unclear clinical significance, as ACTN2 has a strong N-terminal homodimerization domain, the prerequisite for ALK activation by fusion (34), and additionally ALK has been reported to be expressed in a high percentage of Ewing Sarcomas (35). Regarding the candidate FOXO1-NKAIN2 fusion, NKAIN2 is a poorly characterized candidate tumor suppressor gene; fusions and translocations that have been previously reported for this protein are typically either inactivating or out-of-frame (36). FOXO1 fusions to PAX3 or PAX7 include the FOXO1 C-terminal transcriptional activation domain (TAD), aberrantly activating PAX3/7 targets (37).…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that a chromosomal translocation involving this gene was a cause of lymphoma. 19 Angiopoietin 2 encoded by ANGPT2 is an antagonist of angiopoietin 1 and thus disrupts its vascular remodeling ability which may induce endothelial cell apoptosis. 20 However, so far, there has been no report to show the association between SCAR or drug adverse reaction and NKAIN2 or ANGPT2 .…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Therefore, it is very likely that the role of miR-181d, whether as oncogene or tumor suppressor, may be well determined by inverse regulation on its downstream target genes in different cancers. As for gene of NKAIN2, though it was implicated in previous studies that it might act as tumor suppressor, 15,16 or oncogene in human cancer, 17 our study is the first one to reveal its predominant tumor-suppressive role, as well as its close correlation with miR-181d regulation in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 75%
“…15 In various human cancers, NKAIN2 gene is found to be recurrently truncated, possibly located in the 6q commonly deleted region. 15 It was suggested that NKAIN2 might act as a tumor suppressor in human cancer as it induces chromosome loss, mutation, and promoter methylation. 15,16 Interestingly, in another human cancer, NKAIN2 was found to be highly expressed in cancer cells of neuroblastoma and subsequently downregulated in retinoic acid differentiation, thus suggesting an oncogenic role in neuroblastoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation